Body composition, protein and energy efficiencies, and requirements for growth of F1 Boer x Saanen goat kids - Teixeira, I. A. M. A. [UNESP]; Fernandes, M. H. M. R. [UNESP]; Pereira Filho, J. M.; Canesin, R. C. [UNESP]; Gomes, R. A. [UNESP]; Resende, K. T. [UNESP] (Amer Soc Animal Science, 2017)
We conducted a study in which body composition, energy and protein requirements, and efficiency of MP and ME were determined in F1 Boer x Saanen goat kids of 5 to 25 kg BW by using the comparative slaughter technique. Two experiments were performed: Exp. 1 estimated the maintenance requirements of kids from 15 to 25 kg BW, and Exp. 2 estimated the gain requirements of kids from 5 to 25 kg BW. In Exp. 1, 28 intact male F1 Boer x Saanen goat kids were utilized, with 7 kids slaughtered (BW of 15.0 +/- 0.35 kg) at the onset for estimation of initial body composition and the remaining 21 kids assigned to a randomized block design. Within each block, kids were subjected to 3 levels of feed intake treatments (ad libitum [100%] or restricted to 70% or 40% ad libitum). All kids in each block were slaughtered when the animals fed ad libitum reached 25 kg BW. The NEm, ME for maintenance, and partial efficiency of use of ME for NEm were 321.6 kJ/kg(0.75) BW, 525.9 kJ/kg(0.75) BW, and 0.61, respectively. The net protein and MP for maintenance were 2.43 g/kg(0.75) of BW and 4.41 g/kg(0.75) of BW, respectively; thus, the estimated partial efficiency of MP for maintenance was 0.55. In Exp. 2, 32 intact male F1 Boer x Saanen goat kids were distributed in a completely randomized design and slaughtered at 5.6 +/- 0.85 kg BW (n = 6), 10.0 +/- 0.35 kg BW (n = 6), 15.3 +/- 0.52 kg BW (n = 7), 20.4 +/- 0.66 kg BW (n = 6), and 25 +/- 0.46 kg BW (n = 7). Body composition was then fitted to allometric equations. Body fat composition increased from 37 to 114 g/kg empty BW (EBW; P < 0.001), and body protein composition decreased by 10% (from 203.2 to 180.6 g/kg EBW; P < 0.001) when kids grew from 5 to 25 kg BW. The NEg increased by approximately 60% (from 7.2 to 11.5 MJ/kg of empty BW gain [EWG]; P < 0.001), and the net protein for gain decreased by 10% (from 186 to 166 g/kg of EWG; P < 0.001). The partial efficiency of the utilization of ME to NE for growth was 0.32 (P < 0.0001), and the partial efficiencies of the utilization of ME for the synthesis of protein and fat were 0.19 and 0.59 (P < 0.011), respectively. These results demonstrate that the protein and energy maintenance requirements in young crossbred goat kids are greater than values reported previously in feeding system studies. In addition, their requirements for gain depend on body composition and are driven by efficiencies of deposition.
Keywords: accretion rate; fat; gain; maintenance; metabolizable